Optimized PDMs microfluidic biochips for ESC pluripotency maintenance and cardiac differentiation - Ang, Wee Tong (2017)
Microfluidic technologies have been widely utilized in the research of tissue engineering as it can be used as micro-engineered human tissues or organ models, pathogenic and morphogenetic processes and drug screening platforms. Cardiomyocyte is a promising cell source for cardiac tissue engineering which is derived from pluripotent stem cells such as Embryonic Stem Cells (ESC) and induced Pluripotent Stem Cell (iPSC). Combining cardiomyocytes with microfluidic technologies, a heart-on-a-chip can be developed and used as a high-throughput drug screening platform. Polydimethylsiloxane (PDMS) silicon elastomers were popular for the fabrication of microfluidic chip. However, due to the intrinsic PDMS surface hydrophobicity, it inhibits cell adhesion and therefore surface modification is needed for effective cell adhesion. Thus, all the PDMS surface were treated with polydopamine (PD) and gelatin in this study so to achieve effective cell adhesion. The formulation of PDMS which resulted in different surface properties also affects how the cells behave. For ESC adhesion, proliferation and Embryoid Body (EB) attachment, it was found that the 40:1 PDMS substrate yields a better result as compared to other substrates. Next, the ESC pluripotency were best maintained on the 5:1 substrate while the cardiac differentiation of ESC and EB were most optimal on the 40:1 substrate. Lastly, biochips with two designs were evaluated and it was found that a multi-channel biochip can better support the ESC pluripotency maintenance and cardiac differentiation as compared to a single channel biochip. Therefore, an optimized PDMS microfluidic chip can be developed based on the results for a high throughput drug screening platform.